Risk Factors for Failure in Double-Plate Tube Surgery for Refractory Glaucoma: 25 Years Surgical Experience - Duch S (Dove Medical Press, 2021)
Susana Duch, Carlos A Arciniegas-Perasso, Stefania Piludu, Shirin Djavanmardi, Elena Milla Department of Ophthalmology, Innova Ocular ICO-Barcelona, Barcelona, SpainCorrespondence: Susana DuchInnova Ocular ICO Barcelona, c/Fco Carbonell 42 AT, Barcelona, 08034, SpainTel +34-629370919Email sdt1237654@gmail.comPurpose: To investigate risk factors associated with success and failure in double-plate tube surgery.Methods: This retrospective case-series observational study included 243 consecutive eyes that underwent anterior-segment double-plate tube surgery from 1990 to 2015. Evaluation of the efficacy of the device was based on the final intraocular pressure (IOP) and the need for anti-glaucoma medication. We also assessed success and failure according to risk factors for trabeculectomy and an early hypertensive phase (HP).Results: Preoperative IOP was 37.3± 13.1 mmHg (mean±SD) with 3.0± 0.7 medications. After a median follow-up of 44.3 months, the mean IOP was 14.6± 6.3 mmHg with 0.4± 1.0 medications. The final IOPs ranged from 6 to 21 mmHg in 87.24% of eyes; however, 25.47% required medication. No risk factors studied were associated with surgical failure. Preoperative IOP, glaucoma type, previous surgery, previous anti-glaucoma drugs, implant type, and HP were associated with partial success (p< 0.05). HP and preoperative use of brimonidine reduced the probability of complete success by 66.9% and 68.2%, respectively (p< 0.05). HP was more likely when chronic preoperative prostaglandin analogues were administered (odds ratio [OR] 4.286; 95% confidence intervals [CI] 1.593– 11.529; P=0.0039) and when the tube was located in the posterior chamber (OR 3.561; 95% CI 1.286– 9.861; P=0.0145).Conclusion: Tube surgery is effective and seems to be independent of the major risk factors for glaucoma surgery. However, previous surgery and some chronic preoperative drugs are related to the need for glaucoma medication to achieve the target pressure.Keywords: glaucoma drainage implants, tube shunt, double-plate Molteno implant, glaucoma surgery, hypertensive phase, refractory glaucoma